Legal Protection of Consumers Against Damage & Loss of Packages based on Consumer Protection Law - Herlina Basri; Achmad Miftah Farid; Sayang Bidul (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
The use of the internet for long-distance commerce (online shopping) has increased people's dependence on delivery services, but has also triggered various legal incidents related to package damage or loss. This study aims to analyse legal protection for consumers using delivery services based on the Consumer Protection Law (UUPK) and related regulations, and to assess the compensation mechanism implemented by J&T Express. Using normative and empirical juridical research methods, this study combines positive law studies with field studies to observe sociological facts in society. The results show that consumers have the right to preventive (Article 7 UUPK) and repressive (Article 45 UUPK) legal protection, which is also strengthened by Article 86 of the Commercial Code (KUHD) and Articles 1238, 1244, and 1245 of the Civil Code (KUHPerdata) regarding default. In its implementation, J&T Express provides full compensation according to the value of the goods if the package is insured, while for non-insured packages, compensation is limited to a maximum of ten times the shipping cost. In conclusion, the applicable legal instruments have actually provided adequate protection guarantees, but the settlement of settlements in the field is highly dependent on the insurance scheme chosen, so that higher transparency is needed from business actors and increased consumer awareness regarding their rights and obligations to reduce the number of losses in the future.